Pengembangan Media LAUT (Lompat Aksi Ular Tangga) Pada Pembelajaran Matematika Materi Pengukuran Waktu, Dan Panjang Kelas 4 Di Sekolah Dasar - Mira Destyaningrum; Novanita Whindi Arini (Elementary Teacher Education Program, Majalengka University, 2023)
This study aims to make learning interesting and to assess the feasibility of the SEA media (Snake Ladder Action Jump) in the material for measuring time and length in Grade IV Elementary Schools. The research method used is the ASSURE model development research method (Analyze, State, Select, Untilyze, Response, Evaluation). Media experts gave LAUT a media score of 91.60%, then material experts gave 92.50% and educational experts gave a score of 92%. The results of the small trial were 93% and the large trial obtained 95.68%. And also the pre-test results obtained 54.51% and the post-test results obtained 86.45%. So it can be concluded that the SEA media for material measuring time and length is very feasible to use and also efficient for learning mathematics.